The Sociology Of Environmental Activism Among High School Students: A Study Of Islamic Religious Education, Ecoteology, And The Green School Movement - Muh. Hanif; Naela Wirdianul Ulya (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2026)
The global climate crisis demands the contribution of educational institutions in shaping an environmentally conscious character. This research aims to analyze students' environmental activism at MAN Purbalingga through the integration of ecotheology-based Islamic Religious Education (PAI) and the Adiwiyata School program. Using a descriptive qualitative method, data were collected through observation, semi-structured interviews with the madrasah community, and documentation, which were then analyzed using the Miles and Huberman interactive model. The results show that MAN Purbalingga successfully constructed a solid green ecosystem through the synergy of three main elements: theological strengthening in Akidah Akhlak subject materials (specifically the concept of iffah), social habituation such as the "Jumat Bersih" movement, and formal legality in the madrasah's Budget Work Plan. Sociologically, the majority of students' environmental activism is still in the compliance-driven phase toward authority and highly depends on the quality of physical facilities, such as the integrity of trash bin labels. However, these repeated interactions mechanically transform into positive habituation (habitus). This study provides a dual contribution; theoretically, it offers the concept of "Islamic Ecotheology-Based Environmental Activism," where environmental concern originates from tauhid values and is actualized in real actions. Practically, this research contributes by providing strategic guidelines for madrasah administrators to strengthen the green ecosystem and consistently maintain supporting facilities so that students' ecological piety does not stagnate at the level of formality.